Self-medication in students of the medical school of a university in northern Peru 2023: Automedicación en estudiantes de la facultad de medicina de una universidad del norte de Perú 2023 | 2023年北秘鲁一所大学医学院学生的自我药疗 - Sánchez Chamba, Estefany (2024)
Objective: Describe self-medication and its relationship with sociodemographic characteristics in students of the medical school of a university in northern Peru 2023. Methodology: An observational, cross-sectional and prospective design was used with 301 participants, using the CAuM-ovr questionnaire to collect data. Results: 83.4% of the students self-medicated. The bivariate analysis revealed that belonging to medical school significantly increased the probability of self-medication (p=0.0001, OR=26.4), as did having a salary greater than 1,500 soles (p=0.01, OR= 2,26). The main reasons included symptoms not considered serious enough to see a doctor (39%). Regarding the level of knowledge, a high percentage (94.8%) did not request information about medications and 94% believed in the influence of advertising on their purchasing decisions. Attitudinally, 60.6% occasionally consulted a specialist for health problems, while 58.6% bought medications recommended by advertising. Conclusion: The frequency of self-medication is high among these students, which indicates a continuous risk practice despite their health training. Key words: Self Medication; Students; Schools Medical; Attitudes; Knowledge. (source: MeSH NLM)